(untitled) (Jurnal Bahasa, 2018)
Standard Malay root word has one and the same grapheme h that bears different phonetic values according to the phonetic environment, such as the aspiration consonant / h /: [ h ] at the end of the phonological syllable in the word ubah /ubah/: [ubahh] and the fricative consonant /h/: [h] [ú] at the beginning of the phonological syllable in the word usaha /usaha/: [usaha] [usaúa]. However, these two groups of sounds are not distinguished by some phoneticians of Malay. In addition, there is found a double spelling *hh in the derivatives ending in the suffix -an -an or -i -i, such as *pilihhan and *dikasihhi. According to our written data, these derivatives are formed from the root words ending in the aspiration h [ h ] accompanied by the suffixes mentioned above. Although this double spelling *hh is incorrect in terms of the official spelling rules of Malay, it reflects a fact of pronunciation of the Malay words concerned precisely. We analyzed the phonetic values of the grapheme h-s that are found at the boundary between the root words and the suffix -an -an or -i -i in the derivatives, using a computer-aided acoustical phonetic method. As a result of these analyses it was found that the grapheme h-s in some of the recording data had shown a gemination of consonant, that is the aspiration followed by the fricative in the form of [hh] [hú] in the phonetic environment concerned. It is likely that these phenomena of the gemination of the consonant might create the (mis-)spelling *hh [hh] [hú] among some speakers of Malay. Based on this discovery, a hypothesis was presented on the process of the gemination of the consonant h [hh] [hú] in the derivatives concerned, namely the vocal cords movements that cause the glottis to be opened or to be closed in the process of the articulation of the aspiration followed by the fricative sound. Keywords: aspirated consonants, aspirated vowels, aspiration, geminated consonants, gemination, fricatives, plosives.